A Comprehensive Study on the Scope, Functional Capabilities, and Clinical Impact of Real-Time Health Monitoring Systems in Smart Healthcare Ecosystems - Heena Mehta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Health monitoring technology are rapidly altering the healthcare sector by permitting constant, real-time monitoring of vital physiological data. These systems combine wearable devices, Internet of Things (IoT), wireless communication technology, and data analytics to help preventive healthcare, remote patient monitoring, and chronic illness management. This study examines the current spectrum of health monitoring systems, including their applications, technological underpinnings, advantages, and associated concerns. By way of a mixed-methods research approach encompassing literature review, system design, data collecting, and analysis, the study identifies significant areas of influence and restrictions including data privacy concerns, system interoperability, and user acceptance. The study also looks at future possibilities including artificial intelligence integration, non-invasive sensor development, and blockchain for safe data exchange. The findings highlight the importance of multidisciplinary collaboration and robust regulatory regulations to support the development and deployment of efficient, easily accessible, and safe health monitoring instruments. The research emphasizes the creation of resilient and scalable systems applicable to many healthcare contexts, while examining data processing, communication protocols, network design, and sensor selection. Advanced sensor networks will be essential for future health monitoring, since studies demonstrate significant improvements in monitoring precision, system efficacy, and patient outcomes. The current technique is intended to provide a scalable and efficient solution. Furthermore, it would uphold privacy to provide a safe solution.